ACCOMMODATION OF INSTRUCTIONAL ISSUES IN LEARNING ISLAMIC CULTURAL HISTORY: RECONSTRUCTION OF THE ISLAMIC EDUCATION CURRICULUM THROUGH A RESPONSIVE EVALUATION APPROACH - Zainul Arifin; Welly Kuswanto (Program Pascasarjana UIN Sumatera Utara, 2026)
This study aims to examine the instructional issues in the learning of Islamic Cultural History (SKI) within the Islamic Religious Education (PAI) curriculum and to reconstruct the PAI curriculum through a Responsive Evaluation approach. The urgency of this research lies in the persistent gap between the formal curriculum and actual classroom practice, particularly in the representation of SKI as a subject area that is often perceived as memorization-based and historically disconnected from students' contemporary contexts. Employing a qualitative research design with document analysis and field observation, this study involved PAI teachers and curriculum coordinators at Islamic educational institutions in East Lombok. Data were collected through in-depth interviews, classroom observations, and curriculum document reviews, then analyzed using responsive evaluation indicators developed by Stake (1975) and refined by contemporary scholars. The findings reveal three critical instructional issues: (1) the dominance of transmissive pedagogical approaches, (2) misalignment between curriculum objectives and student learning outcomes, and (3) limited integration of higher-order thinking skills (HOTS) in SKI learning materials. The reconstructed curriculum model proposed in this study incorporates contextual learning principles, multicultural perspectives, and inquiry-based instructional strategies. This study contributes to PAI curriculum development discourse by providing an empirically grounded evaluation framework that bridges policy intent and classroom reality.